Investigating the self-perceived acquired competencies of humanities graduates at a South African university - Botha, P. A.; Botha, A. (South African Journal of Higher Education, 2022)
The primary objective of this study was to investigate the self-perceived competencies acquired by humanities graduates at a South African university. This self-assessment enables graduates to assess their strengths and weaknesses regarding their competencies and estimate their employability. The secondary objective was to measure the employment status of humanities graduates. The study followed a quantitative approach using a cross-sectional survey design. The convenience sampling method was used since the self-administered questionnaire was distributed to graduates at two graduation ceremonies. Independent samples t-tests were done to compare the mean scores on the six dimensions of the competencies scale between gender, schools and degrees. Chi-square tests were done to establish whether there are associations between gender, faculty schools, degrees and employment status. Spearman rank-order correlation was performed to measure the correlations between the six factors of the competencies scale. The six individual competencies that scored the highest means were: “(1) tolerance, appreciation of different points of view, (2) written communication skills, (3) critical thinking, (4) English language proficiency, (5) working in a team, and (6) taking responsibility for decisions”. A follow-up study should be done among employers to determine what competencies they require from humanities graduates.